Prevalence of kidney disease of unknown etiology in agricultural workers, Guatemala - Gerardo Arroyo; Gabriella Soto; Sofía García; Jorge Pérez-Folgar; Paola Bailón; Brenda Acabal; Anita Cocón; Mario Díaz-Moscoso; Federico Nave (Pan American Health Organization, 2023)
Objectives. To determine the prevalence of kidney disease of unknown etiology in banana, melon, and tomato workers in north-eastern Guatemala, and to evaluate the usefulness of a cystatin C blood test for early detection of renal disease. Methods. This was a cross-sectional, farm-based study of 462 agricultural workers conducted from June to September 2021. Epidemiological and demographic characteristics of the workers were collected through a self-administered questionnaire. Blood samples were obtained to determine glucose, creatinine and cystatin C levels. Anthropometric and clinical data were also recorded. Results. The prevalence of kidney disease of unknown etiology was 3.03% (95% confidence interval (CI): 1.36-4.70%) based on glomerular filtration rate (GFR-EPI) < 60 mL/min/1.73 m2, with a significantly higher prevalence in banana workers (5.67%; 95% CI: 2.16-9.18%) than melon workers (p = 0.009) and tomato workers (p = 0.044). Ten workers (2.16%) had reduced kidney function (GFR-EPI 60-90 mL/min/1.73 m2). The levels of cystatin C showed less variability (coefficient of variation 46.4%) than those of creatinine (coefficient of variation 67.0%), and cystatin C levels in cases with abnormal and reduced kidney function were significantly different from cases with normal kidney function (p < 0.001). Conclusions. Surveillance of the health of active farm workers and improvement of working conditions, such as sun protection, adequate hydration, and sufficient breaks, are recommended. The significant differences in cystatin C levels between cases with abnormal and reduced kidney function and those with normal kidney function suggest that cystatin C could be a useful measure for early detection of renal disease.